2014
DOI: 10.4293/jsls.2014.00161
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Stent as Bridge to Surgery in Patients with Obstructive Left-Sided Colon Cancer

Abstract: Objective:We assessed the optimal time interval between endoscopic stenting and subsequent surgery in patients with obstructive left-sided colon cancer.Methods:We reviewed the medical records of patients who underwent endoscopic colonic stenting for obstructive left-sided colon cancer between January 2009 and January 2012. Patients who had successful endoscopic intervention as a bridge to surgery were included in the study. Other variables studied were the duration between endoscopic stenting and surgery, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The optimal interval between colonic stenting and surgery is controversial [ 3 20 21 ]. The patients were usually allowed to take oral intake in our hospital after confirming of successful function of stent and assessment of the patients' bowel function.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal interval between colonic stenting and surgery is controversial [ 3 20 21 ]. The patients were usually allowed to take oral intake in our hospital after confirming of successful function of stent and assessment of the patients' bowel function.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment for malignant colonic obstruction includes emergency surgery, a transanal or transnasal ileus tube, or a colonic stent. Emergency surgery for the obstruction is associated with higher morbidity and mortality than elective surgery, and the creation of a stoma is necessary in most cases .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed a median interval of ten days from stent placement to surgery[ 9 ]. A retrospective study from Turkey concluded that time intervals of seven to nine days after stent placement is sufficient for safe surgery[ 18 ]. However, extending the time interval will lead to better recovery of bowel and nutritional status.…”
Section: Discussionmentioning
confidence: 99%